Production of Biogas from Bio-Degradable Municipal Solid Waste – A Way of Resource Recovery. - Atatiru, Faiza (Kabale University, 2023)
Municipal Solid Waste (MSW) generation is increasing with an increase in population. The rate of solid waste generation was reported to be 0.77kg/person/day with recovery rates from 5-40%. In 2020, the world was estimated to generate 2.24 billion tonnes of solid wastes, amounting to footprint of 0.79kg per person per day. With rapid population growth and urbanization, annual waste generation is expected to increase by 73% from 2020 levels to 3.88 billion tonnes in 2050. According to recent study done on the characterisation of MSW in Kabale Municipality, 100kgs of MSW was considered for the study. 87% of the total this MSW composed of biodegradable component. These included food wastes, garden trimmings, paper waste, wood wastes and other biodegradable components having 0.5%, 94.2%, 2.3%, 0.3% and 2.7% respectively of the total biodegradable components. Considering the percentages obtained above, the three most dominant are food wastes, garden trimmings and paper wastes and these were used for carrying out the exercise. 5kg these three were taken to the laboratory for proximate and ultimate analyses. This comprised of 55% garden trimmings, 23% paper wastes and 22% food wastes. Density (315.73 kg/m3) was done using the Gravimetric Method, Moisture (16.7 Wt %), Volatile Solids (57.1 Wt %) and Ash (20%) were done using the thermo gravimetric Method. A Vario Macro cube elemental analyser was used for the quantification of Carbon, C (52.83 Wt %), Hydrogen, H (5.73 Wt %), Oxygen, O (33.23 Wt %), Nitrogen, N (1.68 Wt %) and Sulphur, S (0.87 Wt %) while Calorific Value (2388 Kcal/kg) was done by the bob calorimeter method. A plastic container (0.12m3) capacity was redesigned to be used as a bio digester. During the design, the following results were arrived at considering an average of 5 persons per family each having a solid waste generation rate of 0.2kg/person/day in Uganda: flow rate of 0.003m3, reactor volume of 0.09m3, TS of 0.2kg of dry matter, VS of 1.78kgVs/m3 and OLR of 0.059 kg Vs./m3. From these results, it can be deduced that the C/N ratio is 31.45 which is within the acceptable limits of 25-35. A mixture of MSW (80%) and cow dung (20%) of the total reactor volume was then fed into the bio digester and the slurry PH values 12.6, 8.9, 4.9, 5.3 7.8 4.0, 4.8, 5.8, 5.9, 5.9, 5.9, 5.8 and 5.8 were recorded with varying masses of the gas storage unit in the first 13 days without introduction of any bio boost into the mixture. This clearly showed that the MSW has the potential to generate biogas under controlled conditions in Kabale Municipality.